Recent reduction in the water level of Lake Victoria has created more habitats for Anopheles funestus - Minakawa, Noboru (BioMed Central, 2008)
BACKGROUND: The water level of Lake Victoria has fallen more than 1.5 m since 1998, revealing a narrow strip of land along the shore. This study determined whether the recent drop in the water level has created additional breeding grounds for malaria vectors. METHODS: The recent and past shorelines were estimated using landmarks and a satellite image. The locations of breeding habitats were recorded using a GPS unit during the high and low lake water periods. GIS was used to determine whether the breeding habitats were located on newly emerged land between the new and old shorelines. RESULTS: Over half of the breeding habitats existed on newly emerged land. Fewer habitats for the Anopheles gambiae complex were found during the low water level period compared to the high water period. However, more habitats for Anopheles funestus were found during the high water level period, and they were all located on the newly emerged land. CONCLUSION: The recent reduction in water level of Lake Victoria has increased the amount of available habitat for A. funestus. The results suggest that the water drop has substantially affected the population of this malaria vector in the Lake Victoria basin, particularly because the lake has a long shoreline that may harbour many new breeding habitats.